Corrections to 'Analytical closed‐form solutions for different configurations of parallel‐coupled microstrip lines'. Issue 3 (1st February 2013) - Abbosh, Amin M.
Abstract : The author noticed that three of the equations that are published in the paper [1] include typos that cause significant confusion to the researchers and engineers who try to use the derived closed‐form model. This letter includes the corrected equations. All the results included in the published paper are correct as they are based on the correct form of the equations.